Determination of photosynthetic pigments in fleabane biotypes susceptible and resistant to the Herbicide Glyphosate - Kaspary,T.E. (2014)
Chlorophylls and carotenoids are the main photosynthetic pigment in plants. In the weeds, the greatest amount of photosynthetic pigments can result in high competitiveness of the species. The aim of this study was to quantify the content of photosynthetic pigments in biotypes of fleabane (Conyza bonariensis) susceptible and resistant to glyphosate, by two different methods, as well as a correlation between chlorophyll content obtained by portable and classical methodology (extractable chlorophyll). An experiment was conducted in greenhouse and laboratory, 2 x 5 factorial scheme, where factor A was equivalent to biotypes of fleabane (resistant and susceptible to glyphosate) and factor B to developmental stages plants (rosette vegetative I, II and III and reproduction). At all stages of development, fleabane plants were evaluated with the portable determiner (chlorophyll content) and then the same leaves were subjected to classical methodology laboratory (extractable pigments). The resistant biotype of fleabane showed higher contents of chlorophyll a, b, and total carotenoids, inferring a greater competitive potential regarding the susceptible population to the herbicide. The portable determiner of chlorophyll showed high correlation with the classical method of determination of photosynthetic pigments, and can thus be used to accurately assess this, saving time and reagents.